2021
DOI: 10.3389/fpls.2021.685187
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Brome mosaic virus-Based Gene Silencing Protocol for Hexaploid Wheat (Triticum aestivum L.)

Abstract: Virus-induced gene silencing (VIGS) is a rapid and powerful method to evaluate gene function, especially for species like hexaploid wheat that have large, redundant genomes and are difficult and time-consuming to transform. The Brome mosaic virus (BMV)-based VIGS vector is widely used in monocotyledonous species but not wheat. Here we report the establishment of a simple and effective VIGS procedure in bread wheat using BMVCP5, the most recently improved BMV silencing vector, and wheat genes PHYTOENE DESATURAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 85 publications
(131 reference statements)
2
11
0
Order By: Relevance
“…It is worth noting that significant silencing of PDS and Chll transcripts is not always accompanied by homogenous phenotypic alterations in systemically infected eggplant leaves (Figures 2 and 4 ). This observation is consistent with previous results showing that VIGS by short PDS ‐insertions (below 120 nt) triggered minimum or no bleaching phenotype in plants infected with modified brome mosaic virus (Wang et al., 2021 ), or barley stripe mosaic virus (Bruun‐Rasmussen et al., 2007 ), although measurements of the respective transcripts levels showed significant reductions. In one of these cases (Bruun‐Rasmussen et al., 2007 ), it was suggested that to trigger a visible bleaching phenotype PDS transcripts levels should be lower than a specific threshold at a certain point in leaf development.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It is worth noting that significant silencing of PDS and Chll transcripts is not always accompanied by homogenous phenotypic alterations in systemically infected eggplant leaves (Figures 2 and 4 ). This observation is consistent with previous results showing that VIGS by short PDS ‐insertions (below 120 nt) triggered minimum or no bleaching phenotype in plants infected with modified brome mosaic virus (Wang et al., 2021 ), or barley stripe mosaic virus (Bruun‐Rasmussen et al., 2007 ), although measurements of the respective transcripts levels showed significant reductions. In one of these cases (Bruun‐Rasmussen et al., 2007 ), it was suggested that to trigger a visible bleaching phenotype PDS transcripts levels should be lower than a specific threshold at a certain point in leaf development.…”
Section: Discussionsupporting
confidence: 93%
“…Ó 2022 The Authors. The Plant Journal published by Society for Experimental Biology and John Wiley & Sons Ltd., The Plant Journal, (2022), 112, 284-293 in plants infected with modified brome virus (Wang et al, 2021), or barley stripe mosaic virus (Bruun-Rasmussen et al, 2007), although measurements of the respective transcripts levels showed significant reductions. In one of these cases (Bruun-Rasmussen et al, 2007), it was suggested that to trigger a visible bleaching phenotype PDS transcripts levels should be lower than a specific threshold at a certain point in leaf development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this approach, systemic infection was achieved in approximately one quarter (~ 28%) of the tested 3- or 8-week-old switchgrass seedlings. This infection efficiency is consistent with other monocot species, where plant susceptibility to viral infection has been shown to be impacted by other factors such as genotype/cultivar, vector chassis, construct design, and growth conditions [ 48 , 49 ]. The relevance of optimizing construct design is exemplified by the instability of the FoMV:PDS construct observed in this study.…”
Section: Discussionsupporting
confidence: 86%
“…Although CRISPR/Cas9 and RNAi protocols have been successfully employed in switchgrass [ 8 , 10 , 11 , 14 , 46 , 47 ] , the complex allotetraploid genome and largely outcrossing nature of switchgrass complicate genetic studies. In this study, we used the FoMV vector and mechanical rub-inoculation, previously established in maize, sorghum, and wheat [ 26 , 48 , 49 ] to achieve VIGS in switchgrass. Using this approach, systemic infection was achieved in approximately one quarter (~ 28%) of the tested 3- or 8-week-old switchgrass seedlings.…”
Section: Discussionmentioning
confidence: 99%